Determination of the Education Index and Improvement Strategies in Jambi Province: Determinasi Indeks Pendidikan dan Strategi Peningkatannya di Provinsi Jambi - Ikhwan Afdloli, Mohammad; Heriberta, Heriberta; Achmad, Erni (Jurnal Paradigma Ekonomika, 2024)
This research analyzes: (1) the development of per capita income, School Participation Rate, poverty, Special Allocation Fund, government expenditure, and the education index in Jambi Province (2002–2022), (2) their influence on the education index, and (3) strategies to enhance the index through the Special Allocation Fund. Using quantitative descriptive methods, data from the Central Statistics Agency, Department of Education, and Regional Development Planning Agency were analyzed. Results show fluctuating trends in key variables and confirm that per capita income, School Participation Rate, Special Allocation Fund, and government expenditure significantly impact the education index. A Strengths-Opportunities strategy is recommended, focusing on: (1) expanding educational access in rural areas, (2) balancing teacher and staff distribution, (3) improving facility audits, (4) enhancing learning processes with better facilities and staff training, (5) fostering community collaboration for conducive environments, and (6) optimizing facility use to improve student outcomes and graduate quality. To improve the education index, local governments should strengthen Dapodik operator capacity through training and enhance coordination between the Department of Education and schools for accurate reporting and facility planning.